How Women Engage Homegrown Terrorism. (October 2014) - González, Alessandra L.; Freilich, Joshua D.; Chermak, Steven M.
U.S. Extremist Crime Database (ECDB) Study data of homicides by far-right extremists and arsons and bombings by environmental and animal rights extremists suggest that compared with men, relationships are catalysts for women's involvement in domestic terrorism; recruitment and opportunity differ by ideology and are not always effective in victimizing their intended hate group. We suggest an inter-disciplinary approach that considers criminological principles of strain theory along with sociological emphasis on gendered social networks and the strength of weak ties.